Non-recourse project financing for concentrated solar thermal power. (October 2019) - Geroe, Steven
Abstract: Non-recourse project financing can play a significant role in scaling up total investment in concentrated solar thermal power (CSP). Non-recourse project financing is designed to identify, allocate, and mitigate risks through project structuring and contracting. These techniques can be utilised to address risks specific to CSP projects. Complementary de-risking techniques, such as debt guarantees, can facilitate non-recourse project financings at bankable levels of return in higher risk contexts. Technological advances and learning through global industry scale-up have delivered major reductions in CSP plant development costs. Ambitious CSP targets in China and other jurisdictions underpin future CSP market development. Hybrid off-take models in current utility-scale CSP projects are utilising thermal storage technology to sell rapid response dispatchable power into electricity wholesale markets at peak periods, enabling lower long-term PPA prices at other times. These developments underpin CSP as cost-competitive with solar PV with battery storage and other forms of low emissions technology. Based on an analysis of selected CSP non-recourse project financings, an emerging contractual model of non-recourse project financing risk mitigation and complementary de-risking measures is identified. While the key features of this model are applicable to large-scale projects in developing countries, it is adaptable to meet the requirements of a wide range of projects. In this way, non-recourse project financing can play a pivotal role in the feasibility of large-scale projects in a potentially critical technology for low-carbon energy development that may otherwise be difficult to finance.